Environmental knowledge and attitude as catalysts to promoting environmental practices among senior secondary students in Ondo West Local Government Area, Nigeria (2020)
This study investigated the relationships between environmental knowledge, environmental attitudes and environmental practice. The survey was conducted involving three hundred (300) Students from ten (10) Senior Secondary Schools (both private and public). A self-constructed questionnaires on Environmental knowledge Test (EKT r—0.71), Environmental Attitude Scale (EAS r=0.78) and Environmental Practice Scale (EPSr~0.73) were used to elicit information from student. The data obtained were analyzed using SPSS Windows version 22.0 for Percentage, Mean, Standard Deviation, and Pearson Product Moment Correlation (PPMC). The findings showed that there was students ’ environmental knowledge (r--.022) and environmental attitude positively and negatively correlated with environmental practice, respectively. It was recommended that Environmental Education should be introduced into school curriculum, while a progressive climb of Environmental Ladder Chari should be embraced by campaigning for environmental literacy.